Development Savings Bank: An institutional device to promote economic development and assist in the provision of social justice in Asian countries within the framework of democracy; some basic problems of underdeveloped countries - Loganathan, C. (Colombo : Ceylonese National Council, International Chamber of Commerce, 1959)
The author gives substance to the phrase "democratic socialism", as opposed to the doctrinaire "socialism or capitalism", having as his objective a wide diffusion of economic power instead of a concentration of economic power in the hands of the state or a small capitalist class.
osc 5/9/17
Loans
Keywords: Development banks